Pendampingan Peserta Didik dalam Proses Pembelajaran SMP Istiqomah Sambas Purbalingga - Ahmad Khoiri (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2022)
The teaching and learning process in schools must be in accordance with the characteristics of students in order to achieve meaningful and enjoyable learning. Unfortunately, the lack of knowledge of educators about the importance of recognizing and analyzing student characteristics results in the teaching and learning process being not optimal. Characteristics of students include several things, namely: ethnicity, culture, social status, interests, cognitive development, early abilities, learning styles, motivation, emotional development, social, moral, and spiritual development, as well as motor development. The purpose of this study is to describe the values of student characteristics and methods of analyzing student characteristics to achieve meaningful and enjoyable learning. This study uses a literature study or literature review, by collecting data and information through written and electronic documents that can support the writing process and direct observations to the teacher